The imago of Baetodes traverae Mayo, 1972 (Ephemeroptera: Baetidae), with a redescription of the nymph - Velásquez-Rodríguez, Karen; Huamantinco, Ana A.; Nieto, Carolina (Zootaxa, 2022)
Male imago of Baetodes traverae is described and its nymph is redescribed. The male imago is distinguished from the other known species of the genus by (1) abdominal tubercles absent, (2) turbinate eyes moderately large and not contiguous apically, (3) segment II of forceps without constriction, (4) coxal gills absent, and (5) abdominal tubercles absent. Baetodes traverae nymph is redescribed, with new illustrations aiming to improve the original description done by Mayo (1972). Its nymph has the following characters: (1) terminal filament very short, less than half the length of abdominal segment X, (2) labium with glossae very short, less than half the length of paraglossae, (3) labrum expanded laterally, with submarginal row of four setae, (4) coxal gills absent and (5) abdominal tubercles absent.